Perioperative Management of Metastatic Paraganglioma-Pheochromocytoma of the Humerus with the Aid of Regional Anesthesia. (11th December 2020) - Muse, Iyabo O.; Vivek, Kumar; Bloomgarden, Noah A; Singla, Amit; Geller, David S.
Abstract : A 38-year-old female with a past history of pheochromocytoma and subsequent malignant paraganglioma presented with right arm pain after a fall. Imaging demonstrated a malunited humeral shaft associated with a large cortical destructive lesion and extraosseous extension. Here, we report the use of a multidisciplinary team approach including an endocrinologist, anesthesiologist, and orthopedic surgeon in the perioperative management of a patient with metastatic paraganglioma undergoing a surgical resection of the humerus, internal fixation, reconstruction, and placement of endoprosthesis. The challenges of perioperative anesthetic management and the use of regional anesthesia, especially peripheral nerve block for perioperative pain management, are highlighted.